2006
DOI: 10.2106/jbjs.f.00856
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Contraindications, and Pitfalls of Patellofemoral Arthroplasty

Abstract: Introductionecently, there has been renewed interest in patellofemoral arthroplasty, with the development of newer designs that have produced more consistent outcomes; however, historically, the reported results of this procedure have varied widely 1 . The purpose of this article is to analyze trends in the published results of this procedure, to identify critical factors contributing to the success or failure of these operations, and to relate the initial lessons that we have learned from our six-year clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 32 publications
1
58
0
1
Order By: Relevance
“…However when the thresholds for moderate or severe pain were included in the analysis the survivorship was 88% at 5-years. These results are nevertheless encouraging and have been emulated by independent centres [19, 22, 24, 27, 28]. Mont et al [19] recently reported on their series at a mean follow-up of 7 years and cited a 95% survival at 5 years but falling to 88% at 7 years.…”
Section: Discussionmentioning
confidence: 72%
“…However when the thresholds for moderate or severe pain were included in the analysis the survivorship was 88% at 5-years. These results are nevertheless encouraging and have been emulated by independent centres [19, 22, 24, 27, 28]. Mont et al [19] recently reported on their series at a mean follow-up of 7 years and cited a 95% survival at 5 years but falling to 88% at 7 years.…”
Section: Discussionmentioning
confidence: 72%
“…Operative treatment: Arthroscopy: 2 randomized controlled trials (165 and 168 patients) were included based on indirect evidence (Moseley et al 2002, Kirkley et al 2008)Chondroplasty, resection-arthroplasty, and lateral facetectomy: 1 prospective case series (50 patients) (Becker et al 2008) and 4 retrospective case series (11–63 patients) (Beltran 1987, Yercan et al 2005, Spak and Teitge 2006, Paulos et al 2008)Extensor mechanism alignment and lateral release: 2 prospective case series (35 and 50 patients) (Alemdaroglu et al 2008, Becker et al 2008), 2 retrospective comparative studies (12 and 48 patients) (Weaver et al 1991, Jacquot et al 2004), and 3 retrospective case series (14–50 patients) (Aderinto and Cobb 2002, Kohn et al 2004, Carofino and Fulkerson 2008)Patellectomy: no studies met the inclusion criteriaTotal knee arthroplasty: 2 matched case-control studies (94 and 54 patients) of total knee arthroplasty for isolated patellofemoral osteoarthritis compared with total knee arthroplasty for tri-compartmental osteoarthritis (Laskin and Van Steijn 1999, Meding et al 2007), 1 prospective case series (24 patients) (Parvizi et al 2001), and 3 retrospective case series (25–47 patients) (Mont et al 2002, Dejour et al 2004, Dalury 2005)Patellofemoral arthroplasty: 3 systematic reviews of case series (538–812 patients) (Leadbetter et al 2005, 2006, Becher et al 2008), 5 prospective case series (15–240 patients) (Arnbjornsson and Ryd 1998, Tauro et al 2001, Merchant 2004, Ackroyd and Chir 2005, Ackroyd et al 2007), and 16 retrospective case series (12–65 patients) (Arciero and Toomey 1988, Cartier et al 1990, Argenson et al 1995, Krajca-Radcliffe and Coker 1996, Mertl et al 1997, De Cloedt et al 1999, Fink et al 1999, de Winter et al 2001, Smith et al 2002, Kooijman et al 2003, Board et al 2004, Argenson et al 2005, Cartier et al 2005, Merchant 2005, Sisto and Sarin 2006, Gadeyne et al 2008). …”
Section: Resultsmentioning
confidence: 99%
“…50 Various designs followed i.e. 53 Other factors which can adversely affect outcome are patella alta, obesity, chondromalacia, arthrofibrosis, quadriceps atrophy, age less than 40 years and ligamentous instability of the tibio-femoral compartment. 51,52 There has been a resurgence of interest due to improved implant designs, strict patient and prosthetic selection criteria and improved surgical technique.…”
Section: Patello-femoral Arthroplastymentioning
confidence: 99%
“…Aglietti designed a patellar replacement in 1975, later Blaziina and Lubinus introduced a patello-femoral replacement which resurfaced both surfaces. 53 The advantages of patello-femoral replacement are simplicity, bone conservation and preservation of uninvolved tibio-femoral compartment, meniscus and cruciate ligaments. The indications include: • isolated primary arthrosis of the patello-femoral joint • post-traumatic arthritis • patello-femoral malalignment or dysplasia induced degeneration with or without instability • failed extensor unloading procedure • severe symptoms unresponsive to non-surgical treatment and/or failed previous conservative procedures • extensive grade 3 chondrosis (i.e., loss of joint space without osseous deformation of the patello-femoral joint space, particularly pantrochlear, medial facet, or proximal half of patella).…”
Section: Patello-femoral Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation